Exploring the hydrogen bond kinetics of methanol–water solutions using Raman scattering. Issue 44 (10th November 2020) - Li, Fabing; Wang, Ying; Men, Zhiwei; Sun, Chenglin
Abstract : Stimulated Raman scattering was used to clearly show the hydrogen bond kinetics of water–methanol mixed solutions. Abstract : Stimulated Raman scattering (SRS) and spontaneous Raman spectra are both used here to study the hydrogen bond (HB) structure and kinetics of methanol (MeOH)–water mixtures in different volume ratios. We have found that when the volume fraction of MeOH ranges from 0 to 0.27, the HB structure of water molecules is enhanced, originating from the cooperation of the hydroxyl-enhanced HBs in liquid water and the formation of an ice-like structure around the methyl groups. However, when the volume fraction of MeOH goes beyond 0.27, the main Raman peak of water becomes very weak and even disappeared, which reveals that the HB structure of liquid water is weakened. This weakening can be attributed to the H–H repulsion introduced by MeOH salvation derives. Furthermore, some HBs among water molecules are destroyed at a high MeOH volume fraction (⩾0.7) based on the change of C–H vibrations.